Sleep and insulin sensitivity in adolescents at risk for type 2 diabetes - Clark, Emma, author; Shomaker, Lauren, advisor; Lucas-Thompson, Rachel, committee member; Riggs, Nathaniel, committee member; Prince, Mark, committee member (Colorado State University. Libraries, 2023)
Background: Type 2 diabetes (T2D) is a chronic disease that is the 7th leading cause of death in the United States, and rates of adolescent-onset (<20 years of age) T2D are rising. Adolescent-onset T2D is associated with accelerated cardiometabolic comorbidities and shorter life expectancy compared to adult-onset T2D. As traditional behavioral weight loss approaches to T2D prevention show insufficient effectiveness in adolescents, it is critical to investigate novel, potentially modifiable factors that relate to poor insulin sensitivity, a key precursor of T2D. Poor sleep health is one such potentially modifiable contributor to poor insulin sensitivity and consequently, T2D; however, most research on sleep and T2D is in adults, and the specific characteristics of sleep health that relate to poor insulin sensitivity in adolescents at risk for T2D have not been thoroughly investigated. Further, research suggests that individual characteristics related to stress vulnerability, including dispositional mindfulness (i.e., non-judgmental awareness of the present moment) and self-compassion (i.e., treating oneself with an attitude of kindness and compassion), could alter the association of sleep characteristics with insulin sensitivity. In theory, dispositional mindfulness and/or self-compassion may act as a buffer in the association of poor sleep health and metabolic consequences. Thus, the specific research aims of this dissertation project were to determine to what extent objective characteristics of weekday and weekend sleep health, (1a) wake after sleep onset, (1b) sleep onset latency, (1c) time in bed, (1d) sleep duration, and (1e) sleep efficiency, were associated with insulin sensitivity, and (2) to evaluate mindfulness and self-compassion as moderators of the associations between sleep health and insulin sensitivity. Methods: A total of 128 adolescent girls (M ± SD age 14.40 ± 1.81 years) at risk for T2D participated in the cross-sectional, baseline phase of a parent study. Sleep disturbances were assessed with actigraphy over one week. Mindfulness was assessed with the Mindful Attention and Awareness Scale and self-compassion with the Self-Compassion Scale. The whole body insulin sensitivity index assessment of insulin sensitivity was determined from a 7-draw, 2-hour oral glucose tolerance test. Linear regressions were used to examine the links between sleep characteristics and insulin sensitivity, accounting for the potentially confounding variables of age, BMIz, race/ethnicity, and puberty. Dispositional mindfulness and self-compassion were tested as moderators of the association between sleep characteristics and insulin sensitivity. Results: Despite bivariate associations of insulin sensitivity with weekend wake time after sleep onset and weekend time in bed, after accounting for covariates, there were only two trend-level associations. Specifically, longer weekday sleep efficiency was related to greater insulin sensitivity at trend levels, and longer weekend wake time after sleep onset tended to be related to poorer insulin sensitivity at trend levels, accounting for covariates. Mindfulness and self-compassion moderated the associations of weekend sleep efficiency and weekday sleep efficiency, respectively, with insulin sensitivity at trend levels. Higher weekend sleep efficiency was associated with greater insulin sensitivity, only for adolescents with above-average levels of mindfulness. Higher weekday sleep efficiency was associated with greater insulin sensitivity, but only for adolescents with average or above-average levels of self-compassion. Conclusion: Sleep is an important area for future research in the prevention of T2D in at-risk adolescents. Mindfulness and self-compassion may moderate the associations between adolescent sleep quality and insulin sensitivity; however, these processes need further investigation. A comprehensive understanding of adolescent sleep will advance knowledge of sleep health, insulin sensitivity, and mindfulness/self-compassion in the prevention of adolescent-onset T2D.